Factors associated with readmissions to an adult intensive care unit at a university hospital - Daniele Lopes; Luciana Magnani Fernandes; Débora Cristina Ignácio Alves; Nelsi Salete Tonini; João Lucas Campos de Oliveira (Universidade Federal do Ceará, 2020)
Objective: to verify the rate and factors associated with readmissions in the Intensive Care Unit. Methods: a documentary study, carried out with a sample (n=441) of medical records of adult patients admitted to the Intensive Care Unit of a university hospital. The descriptive and inferential statistical analysis was applied, using Pearson's correlation, the chi-square test, and the t-student test, at a 5% confidence level. Results: most were men (66.2%), with 52.8±18.5 years of age and hospital stay of 10.2±10.8 days. Of these, 29 (6.5%) were readmitted. Death was similar (p=0.893) between readmitted (31.0%) and not readmitted (29.8%). There was no significant correlation between the readmission outcome and age, Nursing Activities Score and time on mechanical ventilation. By comparison, the hospital stay, and extubation were significantly longer (p<0.05) among those readmitted. Conclusion: the rate of readmission was slightly low. Only extubation time was negatively and significantly correlated with the readmission outcome.